2022
DOI: 10.1186/s12969-022-00670-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transitional care programs on adolescent chronic inflammatory systemic diseases: systematic review and meta-analyses

Abstract: Background Patients with juvenile chronic inflammatory systemic diseases (jCID) are vulnerable to many circumstances when transitioning to adult-centered healthcare; this increases the burden of disease and worsen their quality of life. Methods MEDLINE, Embase, Web of Science and Scopus were searched from inception to March 16th, 2021. We included observational, randomized controlled trials and quasi-experimental studies that evaluated a transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…19 In addition, there is sufficient body of evidence that the implementation of transition programs is a determining factor for continuity of care. 20 Some of the results obtained from our survey, although not sufficiently representative, showed that the average age at the beginning of the transition process was between 15 and 17 years for the majority of the respondents, and >18 years in 5% and 30% of the respondents from Brazil and other countries from LATAM, respectively. This demonstrates that we should start the process earlier, if we compare our results, for example, with the NICE guidelines.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…19 In addition, there is sufficient body of evidence that the implementation of transition programs is a determining factor for continuity of care. 20 Some of the results obtained from our survey, although not sufficiently representative, showed that the average age at the beginning of the transition process was between 15 and 17 years for the majority of the respondents, and >18 years in 5% and 30% of the respondents from Brazil and other countries from LATAM, respectively. This demonstrates that we should start the process earlier, if we compare our results, for example, with the NICE guidelines.…”
Section: Discussionmentioning
confidence: 63%
“…These health care transition processes are (1) preparation, (2) transfer of care, and (3) integration into adult health care 19 . In addition, there is sufficient body of evidence that the implementation of transition programs is a determining factor for continuity of care 20 …”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the addition of one more study to the effect size pooling conducted by Moons et al 1 yielded a significant effect on loss to follow-up. Furthermore, a meta-analysis by García-Rodríguez et al, 50 which included various chronic disease populations, also found a significant effect size for clinic drop-out. By combining the results of the previous meta-analysis with the findings of this study, it can be deduced that transition programs may help reduce loss to follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…In a metaanalysis that included adolescents with chronic inflammatory systemic diseases, the use of these programs resulted in significantly fewer hospital admissions during the first 2 years after transition and reduced surgery rates. 76 Finally, it deserves mention that the therapeutic arsenal for pediatric gastroenterologists is more restricted when compared with adult-care providers. Novel drugs undergo testing in the adult patient population, which often gives rise to long lag times between a drug's first approval for adults and the pediatric population.…”
Section: How Has the Evidence-based Treatment Of Pediatric Ibd Evolved?mentioning
confidence: 99%